Discovering compassion in medical training: a qualitative study with curriculum leaders, educators, and learners - Charles B. Lane; Erin Brauer; Jennifer S. Mascaro; Jennifer S. Mascaro (Frontiers in Psychology, 2023)
BackgroundCompassion is considered a fundamental human capacity instrumental to the creation of medicine and for patient-centered practice and innovations in healthcare. However, instead of nurturing and cultivating institutional compassion, many healthcare providers cite the health system itself as a direct barrier to standard care. The trend of compassion depletion begins with medical students and is often attributed to the culture of undergraduate medical training, where students experience an increased risk of depression, substance use, and suicidality.ObjectivesThis qualitative study aims to develop a more comprehensive understanding of compassion as it relates to undergraduate medical education. We used focus groups with key stakeholders in medical education to characterize beliefs about the nature of compassion and to identify perceived barriers and facilitators to compassion within their daily responsibilities as educators and students.MethodsResearchers conducted a series of virtual (Zoom) focus groups with stakeholders: Students (N = 14), Small Group Advisors (N = 11), and Medical Curriculum Leaders (N = 4). Transcripts were thematically analyzed using MAXQDA software.ResultsStudy participants described compassion as being more than empathy, demanding action, and capable of being cultivated. Stakeholders identified self-care, life experiences, and role models as facilitators. The consistently identified barriers to compassion were time constraints, culture, and burnout. Both medical students and those training them agreed on a general definition of compassion and that there are ways to cultivate more of it in their daily professional lives. They also agreed that undergraduate medical education – and the healthcare culture at large – does not deliberately foster compassion and may be directly contributing to its degradation by the content and pedagogies emphasized, the high rates of burnout and futility, and the overwhelming time constraints.DiscussionIntentional instruction in and cultivation of compassion during undergraduate medical education could provide a critical first step for undergirding the professional culture of healthcare with more resilience and warm-hearted concern. Our finding that medical students and those training them agree about what compassion is and that there are specific and actionable ways to cultivate more of it in their professional lives highlights key changes that will promote a more compassionate training environment conducive to the experience and expression of compassion.